Suffering scholars : pathologies of the intellectual in Enlightenment France - Vila, Anne C., 1961- (Intellectual history of the modern age., 2018)
Suffering Scholars focuses on the medical and literary dimensions of the cult of celebrity that developed around intellectuals during the French Enlightenment. Anne C. Vila shows how the ""suffering scholar"" syndrome deeply influenced debates about the consequences of book-learning on both the individual body and the body politic